Annual Update on SDR Trading Operations. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2021)
This paper provides an update on the status of the SDR trading market and operations. In over three decades, SDRs have been exchanged for freely usable currencies in transactions by agreement primarily through the Voluntary Trading Arrangements (VTAs). The VTAs are bilateral arrangements between the Fund and SDR participants or prescribed holders, in which the VTA members agree to buy and sell SDRs within certain limits. A fraction of transactions by agreement-sales or acquisitions of SDRs-were arranged directly between parties.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Monetary Policy; Political Economy; SDR Trading Transaction; SDR Trading, SDR Sales, SDR Acquisitions and Voluntary Trading Arrangements (VTAs); Transparency Policy; VTA Market